Perlindungan Terhadap Pegawai Pemerintah dengan Perjanjian Kerja (PPPK) Melalui Jaminan Hari Tua (JHT) - I Gede Ary Setiawan; I Gusti Bagus Suryawan; Indah Permatasari (Jurnal Konstruksi Hukum, 2022)
Indonesia is one of the countries that prosper its people by providing guarantees provided by the government, namely the Old Age Security (JHT), this guarantee for formal workers who have entered an unproductive age, protection for workers, especially PPPK, and guarantees that Old Age Security (JHT) participants get money to cash in case of retirement, permanent total disability, or death in the ASN Law. The formulation of these problems, including Regarding the arrangements related to the Old Age Security Rights (JHT) for Government Employees with Work Agreements (PPPK) and Related to the mechanism of providing Old Age Security Rights (JHT) for Government Employees with Work Agreements (PPPK) In this study is normative legal research with a statutory approach and legal concept analysis approach. This research concludes that the regulation related to Old Age Security Rights (JHT) for PPPK is regulated in Article 106 paragraph (1) of Law no. 5 of 2014 concerning State Civil Apparatus, Article 75 PP No. 49 of 2018 concerning Management of Government Employees with Work Agreements and the Mechanism of Granting Old Age Security (JHT) for PPPK is regulated in Article 106 of Law no. 5 of 2014 concerning State Civil Apparatus.